Microbial Biodiesel Production by Direct Transesterification of Rhodotorula glutinis Biomass - I-Ching Kuan; Wei-Chen Kao; Chun-Ling Chen; Chi-Yang Yu (Energies, 2018)
(1) Background: Lipids derived from oleaginous microbes have become promising alternative feedstocks for biodiesel. This is mainly because the lipid production rate from microbes is one to two orders of magnitude higher than those of energy crops. However, the conventional process for converting these lipids to biodiesel still requires a large amount of energy and organic solvents; (2) Methods: In this study, an oleaginous yeast, Rhodotorula glutinis, was used for direct transesterification without lipid pre-extraction to produce biodiesel, using sulfuric acid or sodium hydroxide as a catalyst. Such processes decreased the amount of energy and organic solvents required simultaneously; (3) Results: When 1 g of dry R. glutinis biomass was subject to direct transesterification in 20 mL of methanol catalyzed by 0.6 M H2SO4 at 70 °C for 20 h, the fatty acid methyl ester (FAME) yield reached 111%. Using the same amount of biomass and methanol loading but catalyzed by 1 g/L NaOH at 70 °C for 10 h, the FAME yield reached 102%. The acid-catalyzed process showed a superior moisture tolerance; when the biomass contained 70% moisture, the FAME yield was 43% as opposed to 34% of the base-catalyzed counterpart; (4) Conclusions: Compared to conventional transesterification, which requires lipid pre-extraction, direct transesterification not only simplifies the process and shortens the reaction time, but also improves the FAME yield.